The mental health of prison guards: a mapping of Brazilian studies (Research, Society and Development, 2022)
Objective: the study aims to know the main factors that influence the mental health of prison guards. Methods: descriptive study, from integrative review. The inclusion criteria were: studies published between 2014 and 2021, with full text available, in the Portuguese language. The literature search occurred between October and December 2021, in the electronic bases: Virtual Health Library (VHL), Google Scholar, Scielo and Periódico Capes. Seventeen articles were selected for discussion. Results: 2019 was the year with the highest number of publications, nursing and psychology present them selves as the professions with the highest number studies. After reading and textual analysis, four categories emerged for discussion about the theme: Profile of prison system professionals; Impact on quality of life at work perceived by professionals; Vulnerability to psychosocial risks; Being a prison system agent. Conclusion: although job satisfaction is mostly described, a tendency to wards dissatisfaction is observed.